Scuffing propagation of heavily-loaded, lubricated, coated friction joints - Michalczewski, Remigiusz; Piekoszewski, Witold; Tuszynski, Waldemar; Szczerek, Marian (International Conference on Plasma Surface Engineering, 2013)
There is great interest in improving the wear and friction of a wide variety of machine components, e.g. gear systems, gears. In modern technology, due to the increase of the unit pressure, velocities, and hence temperatures in the tribosystems of machines, a risk of a very dangerous form of wear exists. This form is scuffing. The most effective way of to improve the mechanical properties of various engineering components is the modification of surface properties by the deposition of PVD/CVD coatings. In literature, the problem concerning whether it is the most beneficial to coat only one or both of the contacting surfaces and on when and how the coatings may improve the tribological situation in heavily loaded lubricated friction joints is not solved [2, 3]. The aim of this paper was to explore the mechanisms of scuffing propagation of heavily loaded friction pair elements coated with a low-friction WC/C coating for various material combinations.